Richtlinienkonforme Auslegung und Fortbildung von Tarifverträgen - Münder, Matthias (Schriften zum Sozial- und Arbeitsrecht, 2021)
»Interpretation of Collective Bargaining Agreements in Conformity with EU Directives« National statutes must be interpreted in conformity with EU Directives. This dissertation explores whether national courts are obligated to also interpret collective bargaining agreements in conformity with directives according to Article 288 (3) TFEU or German national law. Collective bargaining agreements, on the one hand, often influence employment relationships in a similar fashion as statutes. On the other hand, these agreements are negotiated by private parties on whom directives in general may not impose obligations.